Is There An Association Between Chronic Urticaria and Fibromyalgia Syndrome? - Pelin OKTAYOĞLU,; Derya UÇMAK,; Mehmet ÇAĞLAYAN,; Demet UÇAR,; Mehtap BOZKURT,; Serda EM,; Levent YAZMALAR,; Kemal NAS, (Archives of Rheumatology, 2014)
Objectives: Chronic urticaria (CU) and fibromyalgia (FM) are different types of diseases with unclear etiopathogeneses but share many clinical and histochemical features. This study aims to make a recognization on these features and examines whether patients with CU are also affected by FM. Patients and methods: Forty patients with CU and 38 healthy controls were enrolled to this study. All of the participants were assessed according to the 1990 American College of Rheumatology (ACR) classification criteria for FM and asked questions regarding the clinical features of FM. The quality of life was assessed by the Nottingham Health Profile (NHP), while the psychological status was evaluated using the Hospital Anxiety and Depression Scale (HADS). Results: The incidence of FM was higher among the patients with CU (32.5%) than the controls (10.5%) (p=0.019). We indicated that the patients with CU suffered restrictions regarding to quality of life as assessed by the NHP. NHP-sleep (p=0.035), NHP-social isolation (p=0.032) and NHP-emotional reaction (p=0.027) scores were significantly higher compared to HCs. The HADS-depression scores were also significantly higher in the patients with CU (p=0.006). The patients with CU and concomitant FM had higher total NHP scores than those without FM (p<0.001). Conclusion: Clinicians must be alerted to the possible coexistence of FM in CU patients. Patients with CU have higher rates of FM than the general population and this results in more restrictions in daily life in these patients than those with CU alone. Therefore, additional treatment protocols may be required to be implicated for the treatment of patients with both CU and FM.